2007
DOI: 10.1093/ndt/gfm836
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease in HIV-seropositive patients in Nigeria: an assessment of prevalence, clinical features and risk factors

Abstract: In order to determine the pattern of renal disease and risk factors for renal disease in HIV-infected Nigerians, we studied 400 consecutive HIV/AIDS patients (210 males, 190 females) aged between 18 and 65 years (mean +/- SD; 34.6 +/- 9.4 years), and examined renal disease factors attributable to the infection. Diagnosis of renal disease was based on the consistent presence of at least 1+ albuminuria and/or elevated serum creatinine (>132 micromol/l) as well as the absence of other identifiable causes of chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
78
8
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 15 publications
28
78
8
4
Order By: Relevance
“…According to Emem et al a low Body Mass Index was associated with kidney disease in HIV infected patients (p<0.001) [9]. Indeed, more than half of patients (59.2%) in this study were thin.…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivsupporting
confidence: 42%
See 4 more Smart Citations
“…According to Emem et al a low Body Mass Index was associated with kidney disease in HIV infected patients (p<0.001) [9]. Indeed, more than half of patients (59.2%) in this study were thin.…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivsupporting
confidence: 42%
“…Emem had found that age was associated with chronic kidney failure (p=0.016). He noted that more patients are older; more the risk to chronic kidney failure appears [9].…”
Section: Factors Associated With Chronic Kidney Failure Among Hiv Patmentioning
confidence: 99%
See 3 more Smart Citations